Lower serum magnesium level is an important risk factor for erythropoiesis-stimulating agents hypo-responsiveness in hemodialysis patients - Hayam Hebah; Shaimaa Abdelmegied; Dina Osman; Lina Khedr (The Egyptian Journal of Internal Medicine)
Abstract Purpose There is an established inverse association between serum magnesium levels and anemia in the general population. However, limited information is available about this association in patients on hemodialysis. This study investigated the relationship between serum magnesium and anemia in prevalent hemodialysis patients and its relation to erythropoiesis-stimulating agents (ESAs) hyporesponsiveness. Methods A cross-sectional observational study included 80 prevalent hemodialysis patients. Laboratory data were measured over 3 months. Study populations were divided into 2 groups; group A (n = 34) with serum Mg ≤ 2.2 mg/dl and group B (n = 46) with serum Mg > 2.2 mg/dl. The erythropoietin resistivity index (ERI) was calculated for all patients. Results There were significantly lower mean hemoglobin levels in patients with normo-hypomagnesemia vs patients with hypermagnesemia (8.96 ± 0.44 Vs 9.51 ± 0.39 g/dl respectively), with a p-value < 0.001. ERI mean values were (13.63 ± 3.17 Vs 10.52 ± 2.74 IU/week/kg) which was also found to be a significant p-value < 0.001. Patients with normo-hypomagnesemia had more dialysis-associated symptoms (tremors, weakness, and muscle cramps) (p-value < 0.001). Low serum magnesium was positively correlated with hemoglobin and transferrin saturation (p-value 0.019, 0.001) respectively while it negatively correlated with PTH and ERI (p-value < 0.001, 0.001) respectively. Multivariate analysis revealed that low serum magnesium has been an independent risk for ERI 5 times with odds ratio (OR = 5.159 and p-value < 0.001). Conclusion Lower serum magnesemia is an important risk factor for ESAs hypo-responsiveness with more dialysis-associated symptoms.